Students’ Attitudes Towards Research at Mazandaran University of Medical Sciences in 2015 - Siamian, Hasan (Mater Sociomed, 2016)
BACKGROUND: In today’s world, one of the criteria of progress in a country is research. In our country instead of paying to the research and study, attention is given to the training of human resources. Therefore, this study aimed to investigate Students’ Attitudes towards Research at Mazandaran University of Medical Sciences in 2015. METHODS: In this cross-sectional study the data tool was questionnaire given to the study subjects. The study population were all the paramedical college students at Mazandaran University of Medical Sciences selected. Cochrane methodology was used to determine the sample size, the t test used to know the attitudes and the ANOVA test to assess differences between the groups. RESULTS: The mean age of the students was 20 years (age range of 17 to 32 years), of them, 99 (61%) were female and 63 (39%) male, 100% undergraduate and 73% on their first semester. Their attitudes toward the usefulness of search for jobs and careers, anxiety, relationship with everyday life and Research problem was positive. Belief in research problem with the highest average and relation with everyday life with the lowest average, ranked the highest and lowest scores respectively. The findings also showed that there was insignificant difference between the variables of age, gender and level of education and the attitude of students towards research. CONCLUSION: The subjects under study had Positive attitude to research and in case of availability of research facilities, students would be more interested in performing research.